Heidegger and rhetoric - Gross, Daniel M., 1965-; Kemmann, Ansgar (SUNY series in contemporary continental philosophy., 2005)
"Featuring essays by renowned scholars Michael J. Hyde, Theodore Kisiel, Mark Michalski, Otto Poggeler, and Nancy S. Struever, this book provides the definitive treatment of Martin Heidegger's 1924 lecture course, "Basic Concepts of Aristotelian Philosophy." A deep and original interview with philosopher Hans-Georg Gadamer, who attended the lecture course, is also included. Conducted over the course of three years, just prior to his death in 2002, the interview is Gadamer's last major philosophical statement. By carefully considering this lecture course in the context of Heidegger's life and work, the contributors compel us to reconsider the history and theory of rhetoric, as well as the history of twentieth-century continental philosophy."--Jacket